Association of muscle health and quality of life in older adults living in rural community - Hanan, Nur Andriana Sufea (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2021)
Poor muscle health that includes muscle strength, muscle mass and muscle function may cause a person to have poor quality of life. The aim of this study is to identify and describe the association of the muscle health and quality of life in older adults living in rural area. We recruited only six participants (two men) , mean age of 65.5±6.3 years, from the rural area, Mukim Nibong, Kelantan due to Covid-19 movement restriction orders. Their muscle strength, muscle mass and muscle function were measured using handgrip dynamometer, bio-electrical impedance analysis (BIA) and Short Physical Performance Battery (SPPB), respectively. Their quality of life (QoL) was assessed by using World Health Organisation (WHO) quality of life brief questionnaire (WHOQol-BREF) and sarcopenia quality of life (SarQoL) questionnaire. We also assessed participants’ demographics, health history. Overall, only one participant did not have sarcopenia, two were sarcopenic and three have severe sarcopenia. Results showed that age is significantly negatively correlated (p<0.05) with Domain 2 Psychological (WHOQOL-BREF, r = -0.94) and in total SarQoL scores (r = - 0.88) as well as in D1 (Physical and Mental Health, r = -0.89), D2 (Locomotion, r = - 0.89) and D4 (Functionality, r = -0.89). Hypertension is also negatively correlated (p<0.05) with Domain 2 (r = -0.91) and Domain 4 (Environment, r = -0.89) of WHOQOL-BREF and D1 (r = -0.89), D2 (r = -0.89), D4 (r = -0.89) and overall SarQoL scores (r = -0.88). Type 2 diabetes is significantly correlated with D5 (Activities of daily living, r = -0.98, p = 0.017). BIA lean muscle (r = -0.84) and fat (r = 0.84) is significantly correlated (p<0.05) witth Domain 3 (Social relationship, Poor muscle health that includes muscle strength, muscle mass and muscle function may cause a person to have poor quality of life. The aim of this study is to identify and describe the association of the muscle health and quality of life in older adults living in rural area. We recruited only six participants (two men) , mean age of 65.5±6.3 years, from the rural area, Mukim Nibong, Kelantan due to Covid-19 movement restriction orders. Their muscle strength, muscle mass and muscle function were measured using handgrip dynamometer, bio-electrical impedance analysis (BIA) and Short Physical Performance Battery (SPPB), respectively. Their quality of life (QoL) was assessed by using World Health Organisation (WHO) quality of life brief questionnaire (WHOQol-BREF) and sarcopenia quality of life (SarQoL) questionnaire. We also assessed participants’ demographics, health history. Overall, only one participant did not have sarcopenia, two were sarcopenic and three have severe sarcopenia. Results showed that age is significantly negatively correlated (p<0.05) with Domain 2 Psychological (WHOQOL-BREF, r = -0.94) and in total SarQoL scores (r = - 0.88) as well as in D1 (Physical and Mental Health, r = -0.89), D2 (Locomotion, r = - 0.89) and D4 (Functionality, r = -0.89). Hypertension is also negatively correlated (p<0.05) with Domain 2 (r = -0.91) and Domain 4 (Environment, r = -0.89) of WHOQOL-BREF and D1 (r = -0.89), D2 (r = -0.89), D4 (r = -0.89) and overall SarQoL scores (r = -0.88). Type 2 diabetes is significantly correlated with D5 (Activities of daily living, r = -0.98, p = 0.017). BIA lean muscle (r = -0.84) and fat (r = 0.84) is significantly correlated (p<0.05) witth Domain 3 (Social relationship,